Evaluating an embedded librarianship project in a Philippine scientific research institution a pilot case study of the University of the Philippines Diliman - Sacramento, Simon Philip R. (School of Library and Information Studies, University of the Philippines Diliman, 2019)
Embedded librarianship, though articulated in literature, is rarely documented and studied in the Philippines. Scientific research institutions, which produce large amounts of data require proper information management in order to work efficiently and thus are prime sites for the implementation of embedded librarianship projects. This study describes the implementation of an embedded librarianship projects in the DNA Analysis Laboratory thru the UP College of Science Library, and evaluates its success using an established model. The results show successful implementation of the project, though there are areas to improve for the embedded librarian in order to fully satisfy the metrics of the model.